Access to health information may improve behavior in preventing Avian influenza among women (Faculty of Medicine Universitas Indonesia, 2011)
Background: Improving human behavior toward Avian influenza may lessen the chance to be infected by Avian influenza. This study aimed to identify several factors influencing behavior in the community. Method: A cross-sectional study was conducted in July 2008. Behavior regarding Avian influenza was measured by scoring the variables of knowledge, attitude, and practice. Subjects were obtained from the sub district of Limo, in Depok, West Java, which was considered a high risk area for Avian influenza. The heads of household as the sample unit were chosen by multi-stage sampling. Results: Among 387 subjects, 29.5% of them was had good behavior toward Avian influenza. The final model revealed that gender and access to health information were two dominant factors for good behavior in preventing Avian influenza. Compared with men, women had 67% higher risk to have good behavior [adjusted relative risk (RRa) = 1.67; 95% confidence interval (CI) = 0.92-3.04; P = 0.092]. Compared to those with no access to health information, subjects with access to health information had 3.4 fold increase to good behavior (RRa = 3.40; 95% CI = 0.84-13.76; P = 0.087). Conclusion: Acces to health information concerning Avian influenza was more effective among women in promoting good behavior toward preventing Avian influenza. (Med J Indones 2011; 20:56-61) Keywords: avian influenza, behavior, gender, health promotion